READING RUSKIN'S CULTURAL HERITAGE conservation and transformation. - Chitty, Gill. ([S.l.] : ROUTLEDGE, 2023)
John Ruskin's critical commentary on culture and society, transformative in his own time, established him as a leading critic of the 19th century. His prescient thinking resonates powerfully with today's issues in cultural heritage conservation. This volume presents his ideas in context, key extracts from his works and future directions for his foundational ideas. Ruskin's passionate responses to the environmental and social changes of his day chime with contemporary ideas on themes like sustainability, ethical production and environmentalism. Though widely recognised as a key figure in preservation history, his heritage work is rarely appreciated in full context and breadth. This volume presents six stimulating essays on Ruskin's readership and reception, his transformative perceptions of heritage futures and provocative writing on cultural landscapes and the arts and crafts. Extracts from both well-known and lesser-known works accompany each chapter to reflect the distinctive vocality of his texts, from his writing on architecture and buildings, to landscape and cultural heritage. The volume offers a richer description of cultural context and meaning than usually afforded to Ruskin's work in conservation and critical heritage studies finding its resonance and relevance. Written for an academic and professional audience in heritage studies and historic building conservation and particularly relevant for cultural heritage management, this is a core text and reference work for undergraduate and postgraduate students in history of art and architecture, heritage studies and architectural/building conservation, also central to interests of cultural historians and scholars of nineteenth-century/Victorian history and literature.
OCLC-licensed vendor bibliographic record.
Keywords: Ruskin, John, -- 1819-1900 -- Political and social views; Cultural property; Historic preservation; Culture; HISTORY / General